Negative Effect of Proton‐pump Inhibitors (PPIs) on Helicobacter pylori Growth, Morphology, and Urease Test and Recovery after PPI Removal – An In vitro Study. Issue 2 (28th July 2015) - Saniee, Parastoo; Shahreza, Somayeh; Siavoshi, Farideh
Abstract: Background: Proton‐pump inhibitor (PPI) consumption does lead to false‐negative results of Helicobacter pylori diagnostic tests such as biopsy culture and rapid urease test (RUT). Materials and Methods: Helicobacter pylori isolates from 112 dyspeptic patients with (56.5%) or without (43.5%) PPI consumption were recruited for examining the negative effects of omeprazole (OMP), lansoprazole (LPZ), and pantoprazole (PAN) on H. pylori viability, morphology, and urease, in vitro. The effect of a sublethal concentration of OMP on bacterial features and their recovery after removal of OMP was also assessed. Results: Of 112 culture‐positive gastric biopsies, 87.5% were RUT positive and 12.5% RUT negative. There was a significant correlation between negative RUT results and PPI consumption ( p  < .05). OMP (minimum inhibitory concentration, MIC 32 μg/mL) and LPZ (MIC 8 μg/mL) inhibited the growth of 78.6% of H. pylori isolates. OMP and LPZ inhibited urease of 90.3% of isolates between 0 and 40 minutes and 54.4% between 20 and 40 minutes, respectively. PAN did not inhibit H .  pylori growth and urease. Three 3‐day (9 days) consecutive subcultures of H. pylori on brucella blood agar (BBA) supplemented with OMP resulted in reduced bacterial viability (1+), compared with control (4+), change of spiral morphology to coccoid, and reduction in pink color intensity in urea agar. Bacterial growth (1+), morphology, and urease test did not improve after the first 3‐day and second 3‐day (6 days) subcultures on BBA. However, relative recovery occurred after the third 3‐day (9 days) subculture and complete recovery was observed after the fourth 3‐day (12 days) subculture, as confluent growth (4+), 100% spiral cells, and strong urease test. Conclusion: Proton‐pump Inhibitors exert transient negative effects on H. pylori viability, morphology, and urease test. Accordingly, cessation of PPI consumption at least 12 days before endoscopy could help avoiding false‐negative results of H. pylori diagnostic tests.